A formação da identidade Batista: efeitos de sentidos do trabalho de missões - Vasconcelos, Edite Luzia de Almeida (2010)
This doctoral research, entitled The Formation of the Baptist Identity: The Meaning Effects of Mission Work, seeks to analyze the work of missions to understand the effects of the Baptist discourse as a mechanism for building the identity of the subject. To this end, we seek to demonstrate the contradictory movement of the subject positions that comprises, at the same time, the unity and the division around the evangelizing speech of God’s word. The corpus analysis allowed to demonstrate that the effects of meaning of Baptist missionary work are meant by the sense of mission and vocation that operate the rejection of the discourse subject in relation to secular work. The analysis also showed that the discourse meaning effects of missions function as the primary speech strategy to organize the meanings it affects, in order to homogenize them, resulting in a refractory discourse in relation to the heterogeneity that constitutes it. Thinking about the meaning and subject constructed as na ideological effect of the illusion of unity and break of the dissymmetry between the earthly and spiritual planes, the analytical exam of the corpus is supported in the theoretical and methodological framework of French discourse analysis.